KEEFEKTIFAN MEDIA VIDEO PEMBELAJARAN UNTUK PEMBELAJARAN MATA KULIAH JURUSAN PENDIDIKAN TEKNIK BANGUNAN PASCA COVID-19 - Zefanya Tristan (CV. ADIBA AISHA AMIRA, 2024)
The use of video tutorial media in the context of learning technological images has become a subject of increasing attention in contemporary education. This research aims to spread the effectiveness of video tutorial media as a learning tool in teaching concepts and skills in technological drawing. This research method uses a quantitative approach with an experimental design of pre-test and post-test control groups. The research subjects consisted of secondary level students who were randomly divided into an experimental group that received learning using video tutorial media and a control group that received conventional learning. Data was collected through learning outcomes tests and student perception questionnaires regarding the use of video tutorial media. Data analysis was carried out using descriptive and inferential statistical techniques. Research findings show that learning using video tutorial media significantly increases students' understanding of concepts and skills in technological drawing compared to conventional learning. Apart from that, the student perception questionnaire showed a positive response to the use of video tutorial media in the learning process. This research makes an important contribution in highlighting the role of video tutorial media in increasing the effectiveness of technology image learning as well as providing recommendations for educational practitioners to integrate technology in innovative learning strategies.